Sampled-data observer-based anti-windup control for singularly perturbed systems with actuator saturation - Yan, Yifang; Yang, Chunyu; Ma, Xiaoping; Zhou, Linna (ISA transactions, 2019)
In this paper, the problem of sampled-data observer-based anti-windup (AW) control for singularly perturbed systems with actuator saturation is considered. A sampled-data observer-based AW controller consisting of a sampled-data observer, controller and AW compensator is proposed for the first time. Based on an ε-dependent Lyapunov–Krasovskii functional and linear matrix inequalities, the three components of sampled-data observer-based AW controller are designed simultaneously, which can reduce the conservatism. Furthermore, a convex optimization algorithm is formulated to obtain a desired stability bound and enlarge the basin of attraction at the same time. Finally, examples are provided to demonstrate the effectiveness and merits of the obtained results. •The proposed controller consists of sampled-data observer, controller and AW compensator.•The three parts of sampled-data observer-based AW controller are designed simultaneously.•The perturbation parameter ε and sampling mode are considered in the new proposed LKF.•The advantages of the proposed method are shown in the ε-bound and the basin of attraction.